Lessons learned about occupation-focused and occupation-based interventions: A synthesis using group concept mapping methodology. (2nd October 2020) - Nielsen, Kristina Tomra; la Cour, Karen; Christensen, Jeanette Reffstrup; Pilegaard, Marc Sampedro; von Bülow, Cecilie; Brandt, Åse; Peoples, Hanne; Jonsson, Hans; Wæhrens, Eva Ejlersen
Abstract: Introduction: Occupational therapy (OT) is based on the core assumption that humans are active beings through engagement in occupations. Within OT, occupation is typically used as primary means and/or ends i.e. occupation-focused and/or occupation-based interventions are employed. Studies evaluating such interventions are limited. Objectives: To synthesize experiences about occupation-focused and/or occupation-based interventions. Hence, to identify, organize and prioritize experiences with employing occupation as a core element in OT intervention studies. Methods: Participants were OT PhD students and researchers involved in studies concerning occupation-focused and/or occupation-based interventions. Group Concept Mapping was applied. Results: Based on 133 ideas, a conceptual model emerged encompassing two overall dimensions concerning 'developing interventions' and 'planning intervention studies', respectively. Moreover, ten themes related to one or both dimensions were defined and 94 ideas across clusters had high importance ratings. Conclusion: Synthesis of participants' experiences indicates that 'doing' as agent of change is a core element of OT interventions. Moreover, a multi-level perspective is needed to reach sustainable changes in doing. Group- and peer-support can work as amplifier for change, and flexibility is important during intervention. Such complex interventions need special design and mixed methods in the development, and evaluation of outcome needs to address occupation.